DITOLAKNYA GUGATAN PERCERAIAN KARENA TIDAK ADANYA SURAT IZIN PERCERAIAN PEGAWAI NEGERI SIPIL - Amelia Chandra Utami; Setyaningsih Setyaningsih (Reformasi Hukum Trisakti, 2021)
Article 1 of the 1974 Law regulates the sacredness of a marriage and a lifelong bond between the two. Article 38 of the UUP explains that marriages can be dissolved due to divorce and court decisions. But not all divorce requests were granted by the court. In the Sidoarjo District Court Decision 158/Pdt.G/2020/PN.Sda, The Judge rejected the dissolving of the marriage between the two doctors who had status as civil servants because there was no divorce permit from the superior which should be attached in the documents as proof. The main issues are: 1) Was the absence of a divorce permit from the superior is the reason for dissolving of the marriage, 2) What were the judge's considerations in rejecting the dissolving of the marriage between Dr. SpOG (K) and Dr. Yz.